Assessment of Future Flood Loss in the Daqing River Basin Based on Flood Loss Rate Function - SHI Rongqing; HUANG Lingmei; LI Jia; SHEN Ao (Renmin Zhujiang)
To identify flood-prone areas in the Daqing River Basin and classify flood risk levels, the Spearman's rank correlation coefficient and the random forest method were employed to analyze the correlation and importance between flood loss rates and influencing factors. Based on the most significant indicator, a flood loss rate function was constructed, incorporating four key factors: precipitation, flood control and disaster mitigation capacity, socio-economic development, and natural resources. By using this function, flood loss under five shared socioeconomic pathways (SSPs) from 2030 to 2050 was estimated. The results indicate that the flood loss rate across provinces and cities is generally positively correlated with precipitation factors but negatively correlated with flood control and disaster mitigation capacity, socio-economic development, and natural resources. The multiple regression function effectively captures the variation pattern of flood loss rates, with a coefficient of determination (R²) ≥ 0.89 and a root mean square error (RMSE) ≤ 0.047 3. Under the rainfall scenarios of 1996 and 2012, future economic flood losses are projected to increase significantly by 392%–452% at maximum, while the number of affected people is expected to decrease, with a minimum reduction of 22%–35%.